Urban quality of life evaluation using land price with Status-Quality Trade-Off theory and ecosystem services - Le, Thuy P.; Hoang, Phe H.; Nguyen, Linh X.; Bui, Tu N.; Pham, Tuan L.; Tran, Binh Q. (International Journal of Strategic Property Management, 2023)
Urban Quality of Life (UQoL) is the main objective of sustainable development in the urban context. It is now widely recognised as a multidimensional concept. The satisfaction provided by the elements related to accommodation, such as housing and land, greatly contributes to the satisfaction with quality of life. Meanwhile, the UQoL also contributes to housing and land prices in cities. Our review shows that most current studies on this interrelationship are limited to several dimensions of UQoL and their impact on housing or land prices. This article will fill the gap by using the land price as an input for calculating a UQoL index from the viewpoint of the Status-Quality Trade-Off theory and ecosystem services. A case study was conducted in Cau Giay District, Hanoi, Vietnam, to create a map of the UQoL index and investigate the interrelationship UQoL – land price. In an ideal condition, this interrelationship should be positive (high/low UQoL index – high/low land price). However, this research revealed two other negative scenarios: “high UQoL index – low land price”, and “low UQoL index – high land price”. These negative scenarios can bring many business opportunities and therefore be interesting for stakeholders in the real estate market.